La difficile reconnaissance du caractère professionnel des atteintes à la santé mentale - Jean-Yves Blum Le Coat; Marie Pascual (Perspectives Interdisciplinaires sur le Travail et la Santé)
Recent developments in the consideration of psychosocial risks, as well as in regulations, jurisprudence and administrative practices have given rise to an improvement in the recognition of mental health damages as occupational accidents or occupational diseases. The formalities to gain this recognition, however, remain complicated for the employees involved because of the procedure complexities, the gap existing between the actors’ (employers, company doctors…) assigned role and actual behavior, last but not least the possible impact of the formalities on the person’s situation. The support offered by people with complementary expertise (doctors, psychologists, jurists…) seems appropriate to avoid reaching deadlock.